Impaired muscle strength may contribute to fatigue in patients with aneurysmal subarachnoid hemorrhage. Issue 1 (March 2017) - Harmsen, Wouter J.; Ribbers, Gerard M.; Zegers, Bart; Sneekes, Emiel M.; Praet, Stephan F.E.; Heijenbrok-Kal, Majanka H.; Khajeh, Ladbon; van Kooten, Fop; Neggers, Sebastiaan J.C.M.M.; van den Berg-Emons, Rita J.
Abstract : Patients with aneurysmal subarachnoid hemorrhage (a-SAH) show long-term fatigue and face difficulties in resuming daily physical activities. Impaired muscle strength, especially of the lower extremity, impacts the performance of daily activities and may trigger the onset of fatigue complaints. The present study evaluated knee muscle strength and fatigue in patients with a-SAH. This study included 33 patients, 6 months after a-SAH, and 33 sex-matched and age-matched healthy controls. Isokinetic muscle strength of the knee extensors and flexors was measured at 60 and 180°/s. Maximal voluntary muscle strength was defined as peak torque and measured in Newton-meter. Fatigue was examined using the Fatigue Severity Scale. In patients with a-SAH, the maximal knee extension was 22% (60°/s) and 25% (180°/s) lower and maximal knee flexion was 33% (60°/s) and 36% (180°/s) lower compared with that of matched controls ( P ⩽0.001). The Fatigue Severity Scale score was related to maximal knee extension (60°/s: r =−0.426, P =0.015; 180°/s: r =−0.376, P =0.034) and flexion (60°/s: r =−0.482, P =0.005; 180°/s: r =−0.344, P =0.083). The knee muscle strength was 28–47% lower in fatigued ( n =13) and 11–32% lower in nonfatigued ( n =20) patients; deficits were larger in fatigued patients ( P <0.05), particularly when the muscle strength (peak torque) was measured at 60°/s. The present results indicate that patients with a-SAH have considerably impaired knee muscle strength, which is related to more severe fatigue. The present findings are exploratory, but showed that knee muscle strength may play a role in the severity of fatigue complaints, or vice versa. Interventions targeting fatigue after a-SAH seem necessary and may consider strengthening exercise training in order to treat a debilitating condition.